Antidiabetic and Anti-inflammatory Effects of Peperomia pellucida Leaf Extract: Modulation of Blood Glucose, IL-1β, and Pancreatic Histopathology in STZ-Induced Diabetic Rats - Oktavia, Ria; Anto, Endy Juli; Siahaan, Jekson Martiar (Indonesian Journal of Medicine, 2025)
Background: Diabetes mellitus (DM) is a significant global health challenge with a rapidly increasing prevalence. Although synthetic antidiabetic drugs remain the standard treatment, long-term use often leads to adverse side effects, prompting exploration of natural alternatives. This study investigated the therapeutic potential of ethanol extract of Peperomia pellucida (L.) Kunth leaves in diabetes management through comprehensive assessment of glycemic control, inflammatory marker (IL-1β), and pancreatic tissue histopathology. Subjects and Method: Thirty male Wistar rats were randomized into five groups (n=6): normal control, negative control (STZ-induced), positive control (STZ+metformin 50 mg/kg BW), and two treatment groups receiving Peperomia pellucida extract at doses of 40 mg/kg BW and 80 mg/kg BW, respectively. After 7 days of treatment, blood glucose levels, serum IL-1β concentrations, and pancreatic histopathology were evaluated. Phytochemical screening was conducted to identify bioactive compounds in the extract. Results: Phytochemical analysis confirmed the presence of alkaloids, flavonoids, tannins, saponins, and phenolics. Blood glucose measurements showed significant intergroup differences on day 0 (p<0.001) and day 7 (p<0.001). The 80 mg/kg BW extract group showed a reduction in blood glucose from day 0 (Mean=312.83; SD=40.92) to day 7 (Mean=281.00; SD=34.86). IL-1β serum analysis revealed significant differences among groups (p<0.001), with lower IL-1β levels observed in extract-treated groups compared to the negative control. Histopathological examination demonstrated improved pancreatic tissue structure in extract-treated groups, especially at higher doses. Conclusion: Ethanol extract of Peperomia pellucida (L.) Kunth leaves exhibits promising antidiabetic and anti-inflammatory properties in STZ-induced diabetic rats, as evidenced by reduced blood glucose, decreased IL-1β levels, and improved pancreatic histology. These findings suggest that Peperomia pellucida (L.) Kunth is a potential candidate for the development of natural therapies for diabetes management.